Synthesis, characterisation and evaluation of novel ferrocene-thiazole derivatives as antiplasmodial agents - Hakizimana, Emmanuel Victor (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2017)
Malaria is mosquito-transmitted disease which continues to pose threat to humanity, despite the efforts undertaken by the scientific community, government entities and international organizations. The major problem is that Plasmodium species have developed resistance against available drugs. In order to counter this problem, antimalarial drugs that are efficacious and with novel mode of action are of great necessity. Thiazole derivatives, in particular aminomethylthiazole analogues, have been shown to exhibit promising antimalarial activity against Plasmodium falciparum strains. Previous studies reported the hit compound MMV010539, which showed good antimalarial activity against both K1 (CQ and multidrug resistant strains) and NF54 (CQ sensitive strain). In this study, MMV010539 was deemed to be as an attractive compound to generate novel analogues by addition of ferrocenyl organometallic unit. The ferrocene based compounds have shown biological activity; and with ferroquine currently in clinical trials there has been increasing research into identifying new ferrocenyl-containing molecules as potential antimalarial agents. Herein, thiazole ferrocene based molecules 3.22a-e were synthesised in low to good yields. Their structural identities were confirmed using conventional spectroscopic techniques (¹H and ¹³C NMR, FT-IR spectroscopy and mass spectrometry). The cell cytotoxicity assay of all final compounds confirmed that all ferrocene-thiazole blends 3.22a-e were non-toxic against HeLa cell lines. However, the in vitro biological assay revealed that despite the absence of cell cytotoxicity these compounds poorly inhibited the growth of Plasmodium falciparum parasite. As the aim was to expand further the structure-activity relationship (SAR) of MMV010539, this study confirmed the previous findings that there is a limited structural modification that could be accommodated as indicated in Figure 3.3 (Panel C). Moreover, the combination of ferrocenyl moiety and various alkylamines resulted in compounds with poor antiplasmodial potency, further suggesting that the free amine (Panel A, Figure 3.3) is important for activity.
Keywords: Plasmodium; Malaria -- Chemotherapy; Plasmodium falciparum; Plasmodium -- Inhibitors; Drug resistance in microorganisms; Thiaszoles